1989
DOI: 10.1159/000118568
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Event-Related Potentials and Selective Attention Impairment in Young Chronic Schizophrenics

Abstract: Somatosensory event-related potentials (SERP) were recorded in 30 chronic young schizophrenic patients and in 15 age-matched controls. Objective SERP parameters were latencies, amplitudes and the determination of areas of the cognitive components N1 and P3 by integration. Highly significantly reduced areas and prolonged latencies of the N1 component and significantly prolonged reaction times (RT) discriminate schizophrenics in psychopathological remitted state from controls. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The stimulus barrier was considered to be exceptionally weak in schizophrenics [28]. Remitted schizophrenics did not show any differences in latencies or amplitudes in an event-related study on SEPs [54], although attention-related reduced areas and prolonged latencies of the cognitive component N1 were observed.…”
Section: Discussionmentioning
confidence: 94%
“…The stimulus barrier was considered to be exceptionally weak in schizophrenics [28]. Remitted schizophrenics did not show any differences in latencies or amplitudes in an event-related study on SEPs [54], although attention-related reduced areas and prolonged latencies of the cognitive component N1 were observed.…”
Section: Discussionmentioning
confidence: 94%
“…These categories represent the primary means by which P300 was elicited, with auditory and visual oddball tasks most often employed. Selective attention paradigms (tasks that require target detection with multiple stimuli presented rapidly) were considerably more difficult and demanding than oddball tasks, with the ''other'' category including bimodal stimuli (Alain, Hargrave, & Woods, 1998;Grillon, Ameli, Courchesne, & Braff, 1991;Rockstroh, Mu¨ller, Wagner, Cohen, & Elbert, 1994;Shelley, Grochowski, Lieberman, & Javitt, 1996), somatosensory stimuli (Bo¨ning, Drechsler, & Neuhauser, 1989;Louza˜& Maurer, 1989), word recognition (Koyama et al, 1994), syllable discrimination , and other nonoddball P300 tasks (Condray, Steinhauer, Cohen, van Kammen, & Kasparek, 1999;Hiramatsu et al, 1984;Strandburg et al, 1994Strandburg et al, , 1997. As indicated in Table 2, the auditory oddball paradigm was employed most often and produced the overall largest d and smallest CI for both P300 amplitude and latency measures.…”
Section: Overview Of P300 Schizophrenia Studiesmentioning
confidence: 99%
“…Cognitive processes associated with somatosensory perception have also been examined (see review in (Chang and Lenzenweger 2004)). For example, it was found that somatosensory stimulation in a group of individuals with schizophrenia was associated with decreased activity in brain regions participating in an attentional network (Boning et al 1989). …”
Section: Introductionmentioning
confidence: 99%